Analisis Yuridis Gugatan Rekonvensi dalam Sengketa Wanprestasi Studi Kasus Putusan No. 34/Pdt. G/2025/PN Bdg - Rakha Subandriyo; Abhinaya Ahmad Raharja; Daniel Ran Simamora; Dwi Desi Yayi Tarina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study seeks to examine the counterclaims, also known as reconvention, presented in a breach of contract case as outlined in Decision Number 34/Pdt.G/2025/PN.Bdg, with a focus on the legal grounds used, the court's reasoning, and the resulting legal outcomes within the context of a construction contract. This study employs a normative legal approach, focusing on the case method by examining court rulings, statutory laws, and related legal writings. The findings indicate that the counterclaim was submitted because the first-stage payment for work that had progressed to 30 percent completion was not fulfilled, even though the payment was made through a blank check. The court viewed the action as a breach of contract and ruled that the Plaintiff's suspension of work in the Reconvention was lawful under the terms of the agreement, resulting in a partial approval of the counterclaim. This study shows that recognizing progress in work can create important legal consequences that lead to the need for payment. However, court decisions often focus on formal proof from written documents, which might not take into account the quality of the work as a key part of fulfilling the contract. Therefore, the counterclaim in this case functions as a means of legal protection and also emphasizes the need to balance legal certainty with substantive justice when addressing disputes in construction contracts.